2006
DOI: 10.1080/08860220600689034
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Trend Changes in Acute Renal Failure—A Tertiary Center Experience from South India

Abstract: ARF in South India differs in some important aspects when compared with data from other parts of the country. Significant trend changes were noted with time even within our center. Acute diarrheal disease was the most common cause of ARF. Leptospiral ARF was on the decline, and drugs, sepsis, and malaria were the emerging ARF causes. The incidence of surgical ARF was on the rise. Despite improvements in antenatal care, obstetric renal failure remained a significant cause of ARF. Hemodialysis became the preferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 11 publications
(15 reference statements)
4
49
2
1
Order By: Relevance
“…Whereas in developed regions elderly patients predominate (4,5), in developing countries, AKI is a disease of the young (14,17,18) and children (19,20), in whom volume-responsive "prerenal" mechanisms are common (21)(22)(23)(24). Although overall mortality seems to be lower than in developed countries (25)(26)(27)(28), this finding is not true across all age groups: In these regions, AKI affects predominantly the young and children and mortality is high (29,30).…”
mentioning
confidence: 99%
“…Whereas in developed regions elderly patients predominate (4,5), in developing countries, AKI is a disease of the young (14,17,18) and children (19,20), in whom volume-responsive "prerenal" mechanisms are common (21)(22)(23)(24). Although overall mortality seems to be lower than in developed countries (25)(26)(27)(28), this finding is not true across all age groups: In these regions, AKI affects predominantly the young and children and mortality is high (29,30).…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The 15 studies incorporated patient series ranging from 20 to 1095 AKI patients each, mean age 39-65 years, and the rates of SORO-ESRD revealed from our analysis in the 15 independent reports demonstrated SORO-ESRD rates from 1% in some series, up to 85% of the AKI series. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] AKI was commonly precipitated by hypovolemia/hypotension, infections/sepsis and exposure to nephrotoxics especially radiocontrast, NSAIDs, aminoglycosides and RAAS blocking agents, ACEIs and ARBs. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] …”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] AKI was commonly precipitated by hypovolemia/hypotension, infections/sepsis and exposure to nephrotoxics especially radiocontrast, NSAIDs, aminoglycosides and RAAS blocking agents, ACEIs and ARBs. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] …”
Section: Resultsmentioning
confidence: 99%
“…42 However, clinical studies have shown that antibiotic therapy is efficient in the early and late phases of the disease. 49 Based on the recommendation of the World Health Organization of 2003, severe leptospirosis should be treated with intravenous penicillin (1,500,000 U every 6h), ceftriaxone (1g once a day), or cefotaxime (1g every 6h), all equally effective. 50,51 Antibiotic therapy should be maintained for seven days.…”
Section: Treatment Antibiotic Therapymentioning
confidence: 99%